The Evolution of Education and Family Life in Algeria: Tradition, Modernisation, and Cultural Continuity - Soltani, Riad (Social Empowerment Journal, 2025)
Family and education in Algeria, are a microcosm of larger societal transformations, and both are an engrossing case study in the interaction between tradition and modernization. This article examines two intertwined facets of Algerian society by tracing the historical evolution of its educational system—from the decentralized, religiously grounded model during the Ottoman era, through the disruptive impact of French colonial policies, to the post-independence reforms aimed at reclaiming national identity—and the transformation of family life in the context of modernisation. Employing a combined historical–thematic and mixed-methods research design, the study integrates archival research, demographic analysis, and qualitative testimonies to reveal how Islamic values, colonial legacies, and socio-economic changes have shaped educational practices and familial structures. The findings highlight the enduring cultural continuity amidst change, as well as the emerging challenges in reconciling traditional practices with contemporary demands.